THE EFFECT OF REGIONAL WEALTH, INTERGOVERNMENTAL TRANSFERS, CAPITAL EXPENDITURE, AND GOVERNMENT SIZE ON REGIONAL FINANCIAL PERFORMANCE IN JAMBI PROVINCE FOR 2019–2024 - Tarigan, Helpiana; Yudi, Yudi; Maysarah , Nyimas Dian (Jurusan Akuntansi FEB Universitas Jambi, 2026)
This study aims to examine the effect of regional wealth level, intergovernmental transfer funds, capital expenditure, and government size on financial performance in regencies/municipalities in Jambi Province during the period 2019–2024. The population of this study consists of all regencies/municipalities in Jambi Province from 2019 to 2024. The sampling technique used is saturated sampling, resulting in 66 data samples. Data analysis was conducted using multiple linear regression analysis with IBM SPSS version 27 as the analytical tool. The results of this study indicate that (1) regional wealth level has no effect on the financial performance of regencies/municipalities in Jambi Province, (2) intergovernmental transfer funds have no effect on the financial performance of regencies/municipalities in Jambi Province, (3) capital expenditure has a significant effect on the financial performance of regencies/municipalities in Jambi Province, and (4) government size has no effect on the financial performance of regencies/municipalities in Jambi Province.